Itsbat Nikah Bagi Pasangan yang Salah Satu Atau Keduanya Meninggal Dunia di Pengadilan Agama Mojokerto - Wibowo, Nyoto; Romli, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research studies the manner of implementation of marriage itsbat in the Mojokerto Religious Court, especially in situations where one or both spouses are deceased, with a focus on the Judgment Establishing Marriage Itsbat Number 111/Revd. P/2022/PA. Mr. Itsbat marriage is a legal step to certify a marriage that has not been formally registered, providing legal clarity for the couple and their offspring. The purpose of this study is to know the legal steps of itsbat marriage in that situation, the legal basis used by judges, and the implementation of related legal rules. Using qualitative research methods and a case study approach, data were collected through observation , interviews, and documentation at the Mojokerto Religious Court. Research findings show that itsbat marriage for a couple who has lost one of the parties is conducted through applications that require careful examination of evidence and witnesses . Judges apply national law and Islamic law simultaneously , with emphasis on the importance of fairness, legal certainty , and legal merit. However, the study also found deficiencies in legal protection, particularly for third parties as well as new facts after the decision . These findings highlight the need for the existence of technical rules and means of administrative restraint so that substantive justice can be strengthened , as well as being a practical guide for the judicial apparatus in dealing with complicated cases of itsbat marriage .